Manajemen Kelas Online Learning Guru SMA Insan Cendekia Gowa - Arismunandar Arismunandar; Sitti Habibah; Merrisa Monoarfa; Nurhikmah H (Caradde)
The purpose of this research is to improve teachers' competence in utilizing online learning technology. The method of implementation is through training and assistance in creating online learning sites using Google Sites. The results showed an increase in teachers' knowledge and skills in utilizing Google Sites for online learning management. Teachers are able to create learning sites that contain materials, assignments, quizzes, and other interactive features. In conclusion, training and mentoring for online website development using Google Sites are effective in improving teacher competence in utilizing online learning technology.